The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2147/ijwr.s4587
|View full text |Cite
|
Sign up to set email alerts
|

Lipid minor constituents in wines. A biochemical approach in the French paradox

Abstract: Abstract:The "French paradox" is the observation that the French suffer a relatively low incidence of coronary heart disease, despite having a diet relatively rich in saturated fats. Several theories have been proposed in order to explain this phenomenon and several debates arose. One of them attributed this phenomenon to the regular and moderate consumption of wine in France. More specifi c, it is thought that the existence of bioactive compounds in wine could have an effect on the cardiovascular system, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 116 publications
0
21
0
Order By: Relevance
“…The beneficial effect of wine versus other alcoholic beverages is mainly attributed to its microconstituents. During the last decades, an effort was made to isolate and identify the biological active compounds that are responsible for the wine's cardio protective effect [7]. Wine consists of a complex mixture of compounds that originate both from the grapes and the fermentation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effect of wine versus other alcoholic beverages is mainly attributed to its microconstituents. During the last decades, an effort was made to isolate and identify the biological active compounds that are responsible for the wine's cardio protective effect [7]. Wine consists of a complex mixture of compounds that originate both from the grapes and the fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…PAF is a potent inflammatory and thrombotic mediator that participates in the initiation and prolongation of atherosclerosis [5,6]. Its inhibition from wine microconstituents could partly explain the cardio protective effect of wine consumption [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the nutrition quality factor comprises major nutrients such as carbohydrates, fats and proteins, as well as minor components such as minerals, vitamins, fibers (Bourne, 2002) and the well studied phenolics or not extensively studied various others (Jiang & Du, 2011;Koike, Li, Liu, Hata, & Nikaido, 2005;Li et al, 2009) or still unidentified minor food compounds. In the last decades many studies have revealed that minor food components such as various lipids (Demopoulos, Karantonis, & Antonopoulou, 2003;Fragopoulou, Demopoulos, & Antonopoulou, 2009;Nasopoulou, Karantonis, Detopoulou, Demopoulos, & Zabetakis, 2014) and phenolics (Del Rio et al, 2013) exert beneficial effects in human health by preventing chronic disease development in humans such as cardiovascular diseases and diabetes type II. In recent years it has been made clear that chronic diseases share common basic pathophysiological mechanisms such as inflammation, thrombosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the release of certain metabolites that can further aggravate the atherosclerotic lesion. Flavonoids can inhibit platelet activation and aggregation through the inhibition of AA activation or blockade of ADP and collagen [71][72][73]. For example, resveratrol in 20 healthy volunteers reported antiplatelet effects as it increased nitric oxide (NO) production, which in turn inhibits platelet aggregation as it causes an increase in platelet NO synthase enzyme activity [74].…”
Section: Cardiovascular Propertiesmentioning
confidence: 99%